The heron's cry - Cleeves, Ann (Cleeves, Ann. Two rivers series., 2021)
"Ann Cleeves-New York Times bestselling and award-winning author of the Vera and Shetland series, both of which are hit TV shows-returns with the extraordinary follow-up to The Long Call, in the Two Rivers series, soon to be a major TV series too. North Devon is enjoying a rare hot summer with tourists flocking to its coastline. Detective Matthew Venn is called out to a rural crime scene at the home of a group of artists. What he finds is an elaborately staged murder--Dr Nigel Yeo has been fatally stabbed with a shard of one of his glassblower daughter's broken vases. Dr Yeo seems an unlikely murder victim. He's a good man, a public servant, beloved by his daughter. Matthew is unnerved, though, to find that she is a close friend of Jonathan, his husband. Then another body is found--killed in a similar way. Matthew soon finds himself treading carefully through the lies that fester at the heart of his community and a case that is dangerously close to home. DI Matthew Venn returns in The Heron's Cry, in Ann Cleeves powerful next novel, proving once again that she is a master of her craft"--